2015
DOI: 10.1038/srep17089
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of strongly enhanced photoluminescence from inverted cone-shaped silicon nanostructures

Abstract: Silicon nanowires (SiNWs) attached to a wafer substrate are converted to inversely tapered silicon nanocones (SiNCs). After excitation with visible light, individual SiNCs show a 200-fold enhanced integral band-to-band luminescence as compared to a straight SiNW reference. Furthermore, the reverse taper is responsible for multifold emission peaks in addition to the relatively broad near-infrared (NIR) luminescence spectrum. A thorough numerical mode analysis reveals that unlike a SiNW the inverted SiNC sustain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
1
22
2
Order By: Relevance
“…To get a better insight into the mechanism which causes the intense and discrete sub‐band gap emission, the mode formation inside a regular GaAs rhombic‐dodecahedron was studied using finite difference time domain (FDTD) simulations (Lumerical) . Therefore, spectra of the relative mode emission intensities for GaAs rhombic‐dodecahedra were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get a better insight into the mechanism which causes the intense and discrete sub‐band gap emission, the mode formation inside a regular GaAs rhombic‐dodecahedron was studied using finite difference time domain (FDTD) simulations (Lumerical) . Therefore, spectra of the relative mode emission intensities for GaAs rhombic‐dodecahedra were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…While optical devices based on silicon (Si) photonics are already well established and approach market maturity, fully integrated Si‐based optoelectronic devices for on‐chip optical interconnects, data processing, and sensing would require a small near‐infrared light source because the Si host medium is strongly absorbing at visible wavelengths . However, since the band‐to‐band transition in Si does not simultaneously obey the laws of energy and momentum conservation, spontaneous emission rates are low as compared with those of direct semiconductors and efficient Si‐based solid state lightning remains challenging . Numerous options to improve the efficiency of Si‐based light emission have been investigated, most of which rely on quantum confinement in integrated nanocrystals, quantum wells or superlattices and the introduction of efficient (quasi‐direct) transitions by sophisticated strain‐ and materials‐engineering methods .…”
Section: Introductionmentioning
confidence: 99%
“…Another way of increasing the external photoluminescence of a nanowire with low is by using the Purcell effect, as has recently been demonstrated by Schmitt et al 163 . By tailoring the local density of optical states around the emitter, the spontaneous emission rate can be enhanced by the Purcell effect into an enhanced emission rate / , in which ∝ is the Purcell factor, Q the cavity quality factor and V the cavity mode volume.…”
Section: Enhanced Open-circuit Voltage By An Enhanced Photon Extractimentioning
confidence: 99%
“…In a solar cell, the Purcell effect can be very useful to enhance the radiative rate relative to the nonradiative loss. Schmitt et al 163 demonstrated whispering gallery modes in an inverted nanocone, with a Q-factor of 1300, and observed a 200x enhancement of the external photoluminescence by this nanophotonic engineering approach.…”
Section: Enhanced Open-circuit Voltage By An Enhanced Photon Extractimentioning
confidence: 99%
“…Previously, researchers argued that these improvements were the result of a combination of in-plane strain relaxation, a decrease in the quantum-confined Stark effect (QCSE), light extraction efficiency enhancement and lateral carrier confinement. 6,[9][10][11] However, detailed analyses of carrier dynamics are still unable to explain the change in luminescence properties of MQW nanorods over planar layers with respect to their carrier density dependence. [12][13][14][15] In particular, the impact of the significant increase of surface states in nanorods is not fully understood.…”
Section: Introductionmentioning
confidence: 99%